EXPERIENCE WITH TITANIUM CAGES IN ANTERIOR CERVICAL DISCECTOMY AND FUSION - Junaid, Muhammad; Rashid, Mamoon Ur; Afsheen, Afeera; Bukhari, Syed Sarmad; Kalsoom, Anisa (Journal of Ayub Medical College Abbottabad, 2016)
Background: Anterior cervical discectomy is a common procedure for treating patients for cervical disc prolapse. This study was conducted to study the surgical outcome and demographic characteristics of patients who were treated for anterior cervical disc prolapse. Methods: Study was conducted in the combined military hospital (CMH) Peshawar. Study interval was 3 years from 1st September, 2011 to 31st August, 2014. Total number of patients were 84. Males were 54 (64.28%) and females were 30 (35.71%). All the patients had undergone the procedure of anterior cervical discectomy and fusion with titanium cages (ACDF). All the patients had plain MRI cervical spine done for diagnosis of anterior cervical disc prolapse. Results: Total 84 patients were operated. In the patients who complained of brachialgia, 100% improvement was seen after the operation. Three (3.5%) of the patients, who presented with axial neck pain, continued to complain of pain and 2 (2.5%) of the patients complained of pain at the donor site after the operation. One of the patient had dural tear which resulted in subcutaneous cerebrospinal fluid (CSF) accumulation and was treated conservatively with repeated aspiration. Fusion rate was 100% with titanium cages used for fusion after anterior cervical discectomy. No complications were noted after the surgery at 1 year of interval. Conclusion: Results with titanium cages are expectedly good. Symptoms resolved and fusion rate was 100% at 1 year follow up.